Targetable ERBB2 mutations identified in neurofibroma/schwannoma hybrid nerve sheath tumors - Ronellenfitsch, Michael Wilfried; Harter, Patrick N.; Kirchner, Martina; Heining, Christoph; Hutter, Barbara; Gieldon, Laura; Schittenhelm, Jens Florian; Schuhmann, Martin U.; Tatagiba, Marcos; Marquardt, Gerhard; Wagner, Marlies; Endris, Volker; et al. (The journal of clinical investigation, 2020)
Neurofibroma/schwannoma hybrid nerve sheath tumors (N/S HNSTs) are neoplasms associated with larger nerves that occur sporadically and in the context of schwannomatosis or neurofibromatosis type 2 or 1. Clinical management of N/S HNST is challenging, especially for large tumors, and established systemic treatments are lacking.
First published February 4, 2020
Gesehen am 02.032020